PENUNDAAN PEMBAGIAN WARISAN: DAMPAK HUKUM DAN SOLUSI PENYELESAIANNYA - Harahap, Taufik Hidayat (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2024)
The delay in inheritance distribution in the Pidie District community is largely influenced by a tradition that requires inheritance to be distributed only after the wife of the heir passes away. Although this is done to maintain family harmony, it contradicts the principles of Islamic law, which dictates that inheritance should be distributed immediately after the heir's death. This study aims to analyze the reasons behind the delay in inheritance distribution and to understand the role of customary law ('urf) in this practice. The research uses a descriptive qualitative method, collecting primary data through interviews, observations, and documentation, alongside secondary data from relevant literature. The findings indicate that the delay is driven by emotional factors and customary practices, despite the potential harm to the heirs, particularly children who should receive their inheritance promptly. From an Islamic law perspective, the delay in inheritance distribution falls under the category of ‘urf fasid, which is not in accordance with Islamic law.